2005
DOI: 10.1016/j.jorganchem.2005.07.072
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and in vitro antimicrobial activity of organotin(IV) complexes with triazolo-pyrimidine ligands containing exocyclic oxygen atoms

Abstract: Tri-organotin(IV) complexes of the triazolo-pyrimidine derivatives 4,5-dihydro-5-oxo-[1,2,4]triazolo-[1,5a]pyrimidine (5HtpO), 4,7-dihydro-5-methyl-7-oxo-[1,2,4]triazolo-[1,5a]pyrimidine (HmtpO), and 4,5,6,7-tetrahydro-5,7-dioxo-[1,2,4]triazolo-[1,5a]pyrimidine (H 2 tpO 2 ), and the diorganotin derivative n-Bu 2 Sn(tpO 2 ), were synthesized and characterized by means of infrared and 119 Sn Mö ssbauer spectroscopy. In all the complexes obtained the triazolopyrimidines act as multidentate ligands producing polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 46 publications
3
18
1
Order By: Relevance
“…Recently, we described complexes of diorganotin(IV) dichlorides with the heterocyclic ligands [1,2,4] [12], 5,7-ditertbutyl-1,2,4-triazolo [1,5-a]pyrimidine (dbtp) and 5,7-diphenyl-1,2,4-triazolo [1,5-a]pyrimidine (dptp) [13] that exhibit antibacterial activity against a group of reference pathogen micro-organisms, thus showing antibacterial activities against a group of reference pathogen micro-organisms, which shows their inhibitory effect. In vitro antimicrobial tests showed that n Bu 2 SnCl 2 (dmtp) [12] has interesting properties as anti Grampositive and antibiofilm agent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we described complexes of diorganotin(IV) dichlorides with the heterocyclic ligands [1,2,4] [12], 5,7-ditertbutyl-1,2,4-triazolo [1,5-a]pyrimidine (dbtp) and 5,7-diphenyl-1,2,4-triazolo [1,5-a]pyrimidine (dptp) [13] that exhibit antibacterial activity against a group of reference pathogen micro-organisms, thus showing antibacterial activities against a group of reference pathogen micro-organisms, which shows their inhibitory effect. In vitro antimicrobial tests showed that n Bu 2 SnCl 2 (dmtp) [12] has interesting properties as anti Grampositive and antibiofilm agent.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro antimicrobial tests showed that n Bu 2 SnCl 2 (dmtp) [12] has interesting properties as anti Grampositive and antibiofilm agent.…”
Section: Introductionmentioning
confidence: 99%
“…The arrangement of the carbon atoms in the Sn(Alk) 3 group can be easily deduced from the tin-carbon stretching modes which occur in the 550-500 cm À1 region of the infrared and Raman spectra [23]. , fully consistent with a trigonal bipyramidal structure with organic groups in the equatorial plane and electronegative ligands in axial positions [24], tin being 5-coordinate.…”
Section: Spectroscopic Datamentioning
confidence: 81%
“…Introduction [1,2,4]Triazolo [1,5-a]pyrimidine derivatives have been extensively used in the synthesis of metal-ion complexes obtaining a variety of new compounds with interesting structural features and relevant biological properties [1,2]. Organotin(IV) complexes were also recently investigated [3,4]. The coordination studies were essentially devoted to alkyl-or oxo-substituted triazolopyrimidines, other substituents being ignored.…”
mentioning
confidence: 99%
“…The aim of this work is to synthesize complexes of Arginine, effector of recognition, with organotin(IV) ions (R 2 Sn 2+ and R 3 Sn antimicrobial [5], anti-inflammatory activities [6]. L-Arginine is an essential aminoacid with a side-chain guanidino group, which is strongly basic and protonated in a wide range of pH values and serves as a biological recognition site through hydrogen bonding [7].…”
Section: Introductionmentioning
confidence: 99%